The Status of Freshwater Crayfish (Astacus leptodactylus Eschscholtz) Fisheries in Turkey - Harlioglu, Ayse Guel; Harlioglu, Muzaffer Mustafa (Taylor & Francis Inc, 2009)
Although there have been fluctuations among years, the harvest of A. leptodactylus in Turkey has increased steadily after 1995. Prior to this increase, the harvest was under the pressure of over-catching, water pollution, and a fungal disease (Aphanomyces astaci Schikora), which was first observed in Turkey in 1984. However, the harvest of A. leptodactylus in Turkey has started to decrease again since 2005. The harvest decreased from 2,317 tonnes in 2004 to 809 tonnes in 2005 and to 797 tonnes in 2006. Furthermore, the harvest decreased to 750-760 tonnes in 2007. An explanation for the reduction in crayfish harvest is not known for all populations. No published reports have attributed the massive mortalities of crayfish due to the fungal disease. Some populations are under the pressure of over-harvesting in some years. The shortage in A. leptodactylus harvest in Turkey, which is one of the main exporters of A. leptodactylus to Europe, has led to the tendency of European consumers to import Pacifastacus leniusculus or Procambarus clarkii from China and America. To increase crayfish production in Turkey, the idea of introducing non-native crayfish species into freshwaters may be encouraged, but these introductions may cause a worse situation because of the well-known adverse effects of non-native crayfish introductions throughout the world. Therefore, government and public authorities in Turkey should focus on a solution to the decrease in crayfish harvest in Turkey, and conservation and management studies of crayfish populations are also critically needed.
Keywords: Astacus leptodactylus; crayfish; fisheries; harvest; population; reduction; Turkey